In the service of learning and empowerment : service-learning, critical pedagogy, and the Problem-Solution Project - Stenhouse, Vera L.; Jarrett, Olga S.; Williams, Rhina M. Fernandes; Chilungu, E. Namisi (Emerald Publishing Limited : Information Age Publishing Inc., 2014)
Too often teachers and students doubt their own abilities to forge collective work and dynamic critical learning in the midst of education reform practices that limit their opportunities to do so. This doubt can be heightened for elementary school teachers or even their students who are led to believe that they are not capable of engaging critically with their education and their world. The Problem-Solution Project erases this doubt through merging service-learning, critical pedagogy, and constructivism. This approach to teaching and learning is designed to empower teachers and students while they meet curriculum standards and actively contribute to the transformation of their world. Unique to this collection are the reported experiences of teacher educators who implement Problem-Solution Projects in their courses; preservice teachers' reflections on cohort-driven Problem-Solution Projects; and first-year and veteran teachers stories featuring Problem-Solution Projects initiated by their PK-5 students. Features include: * Describes how Problem-Solution Projects advance service-learning and critical pedagogy. * Discussion of how Problem-Solution Projects build on curriculum standards but resists standardization of implementation and repressive education reforms. * First-hand accounts of teachers implementing Problem-Solution Projects. * Detailed description of the steps and outcomes of doing Problem-Solution Projects with preservice teachers, inservice teachers, and elementary students. * Examples of Problem-Solution Projects across courses, subjects, disciplines, and contexts. Readers will find worthwhile the theoretical connections and the practical applications. Service-learning, urban education, multicultural education and teacher education, teacher preparation practitioners will find this text beneficial. The main audience: teacher educators across disciplines, pre- and in-service teachers working in elementary (PK-5) settings.